The concept of time in kindergarten (Journal of the College of Basic Education, 2026)
The current research aimed to identify the concept of duration among kindergarten children, and it consisted of a real research of (100) children of a mature age (5-6) years, with (50) children and (50) children in the former first Karkh Directorate in Baghdad, and to achieve the goals of the research on a research tool with effective numbers with the age group that consists of (22) paragraphs and reached a study after statistical intelligences There are differences with a statistical choice of the sample in light of the research results that there are no statistically significant differences with regard to gender change.